Consumers’ response to mass market scam solicitations: profiling scams and responses - Klapatch, Lukas (Psychology, crime & law, 2023)
Mass marketing scams (MMSs) impact millions of people with financial losses in the billions. Understanding what types of MMSs work is key to reducing the compliance rate. Inspired by Simon’s work, we designed an experiment to examine how four different types of MMSs impact interest in and intention to respond to solicitations. We first conducted a cluster analysis on 215 actual MMS solicitations. The analysis revealed four distinct types of solicitations: negative-cold, one-reward letters, high emotionality, high scarcity letters where the prize is mentioned often, very colorful multi-prize letters, and low emotionality, low scarcity cold letters. In a second experiment, 281 participants (recruited on MTurk) were randomly assigned to read one of the four types of solicitations. Our data revealed differences in intention to respond by sending money. Furthermore, younger (vs. older) individuals indicated a higher interest in the solicitation and higher intention to send in money and rated the solicitations as significantly more beneficial and less risky. Finally, perceptions of risks and benefits were the main driving force behind compliance beyond interest and intention to comply. In line with Simon’s ideas, our study highlights the need to examine both the environment (the types of solicitations) and the decision-maker.